Is learning agility important on BUMN Plantation? - Yusniar Lubis; R. Turino Januar Budyanto; Ahmad Rafiki (Jurnal Mantik, 2023)
The purpose of this study was to determine the effect of learning agility on individual performance and Talent Management at PTPN IV, the largest BUMN Plantation with main commodities of CPO and Black Tea. Based on the formulation and the relationship between variables processed using the Partial Lest Square (PLS) Model and Smart PLS 3.0 software to 408 respondents who are employees with managerial positions. The results of the study show that there is a positive and significant influence between learning agility and individual performance and talent management.